HUBUNGAN ANTARA MOTIVASI BERPRESTASI DENGAN DISIPLIN KERJA GURU TAMAN KANAK - KANAK SE-KECAMATAN RAMBAH KABUPATEN ROKAN HULU - indarto, Wusono; ', Mardiah; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Mardiah. The relationship between achievement motivation and discipline Kindergarten teacher Rambah Rokan Hulu. The purpose of this study was to determine whether there is a correlation between achievement motivation and discipline teachers of kindergarten throughout the district Rambah Rokan Hulu. This research is a correlation study, variables consist of two variables: the variable motivation and work discipline variables. The population of all kindergarten teachers Rambah Rokan Hulu district that is about 40 people. Based on research results using statistical analysis has a positive and significant relationship between achievement motivation and discipline Kindergarten teacher Rambah Rokan Hulu. It can be seen from the assessment of the acquisition value test